Social and Cultural Interpretation of the Maleman Tradition in the Sasak Community of Lombok - Usman, Usman (Ulumuna, 2023)
Traditions in society is not only the product of the cultural heritage of a particular community that has been preserved for generations, but also of an interpretation of the transcendental values of teachings derived from the holy text of the Quran. It may also be the result of a marriage between religious understanding and the tradition of its adherents or the relationship between religion and local traditions. In this regard, this study aimed to unveil and analyze the cultural realities within the ‘Maleman’ tradition of the Sasak community as a product of interpreting the Quranic text regarding the night of ‘lailatul qadar’, which was the focal point of this study. Anchored in a phenomenological qualitative approach and an interactive analysis model from in-depth interviews and participant observations, symbolic meanings and religiosity values were discovered within the ‘Maleman’ tradition. It was the result of the Sasaknese community’s interpretation within their cultural landscape that has been preserved to this day. Additional findings indicated that the ritual of lighting the ‘dile Jojor’, a traditional torch made from the castor seeds, on the odd nights of the 21st, 23rd, 25th, 27th, and 29th of Ramadan was intended to welcome ‘laelatul qadar’, which the Sasak community of Lombok believed to be a night that must be ‘pursued’ (QS. al-Qadr [97]): 1-5 and guided by (QS. al-Taghabun [64]): 8. Similarly, the selection of raw materials for ‘Dile Jojor’ from the fruit of the ‘Jarak’ (Castor) tree, symbolically analogized from the term ‘syajarah mubarakah zaituna’ (QS. al-Nur [24]): 35. Both have a common element, namely they contain oil that can produce light.”